Efektivitas Intervensi Edukasi Audiovisual Berpusat pada Keluarga terhadap Pengetahuan dan Pencegahan Delirium di Unit Perawatan Intensif: Studi Kuasi-Eksperimental: FAMILY-CENTERED AUDIOVISUAL EDUCATION FOR DELIRIUM PREVENTION IN ICU - Wenny Trisnaningtyas; Muhammad Triyandinata (Nurse and Health: Jurnal Keperawatan, 2026)
Background: Family involvement is essential in the care of critically ill patients, particularly in preventing and managing conditions such as delirium. However, limited knowledge among family caregivers often hinders effective participation. Audiovisual-based health education has emerged as a promising strategy to enhance understanding through engaging and accessible learning modalities. Objective: This study aimed to examine the effectiveness of audiovisual-based health education in improving knowledge among family caregivers of intensive care unit (ICU) patients. Methods: A quasi-experimental study with a pre-test–post-test control group design was conducted involving 72 participants. Respondents were assigned to either an intervention group receiving audiovisual-based education or a control group receiving standard care. Knowledge levels were measured using a structured questionnaire before and after the intervention. Data were analyzed using the Wilcoxon signed-rank test for within-group comparisons and the Mann–Whitney U test for between-group differences. Results: The intervention group demonstrated a significant increase in knowledge scores from 7.86 ± 2.55 to 16.19 ± 3.46 (Z = 4.949, p < 0.001), indicating a large effect size (r = 0.70). In contrast, the control group showed a non-significant improvement from 4.56 ± 1.78 to 6.28 ± 2.19 (Z = 1.732, p > 0.05). Between-group analysis revealed a significantly greater improvement in the intervention group (Δ = 8.33) compared to the control group (Δ = 1.72) (Z = 7.062, p < 0.001; r = 0.99). Conclusion: Audiovisual-based health education is highly effective in improving caregiver knowledge and represents a practical, scalable strategy for enhancing family engagement in ICU care. Keywords: audiovisual education; knowledge; family caregivers; ICU; delirium